Keefektifan Model Teams Games Tournament (TGT) Berbantuan Media Permainan Ular Tangga Berbasis Misi Terhadap Motivasi dan Hasil Belajar Matematika Kelas III Sekolah Dasar - Yulianti, Dyah Rahmah; Witanto, Yuli (JPDI (Jurnal Pendidikan Dasar Indonesia), 2025)
This study aims to 1) test the difference in learning motivation between learning using the TGT model assisted by mission-based snakes and ladders media and learning using the PBL model assisted by learning video media; 2) test the difference in learning outcomes between learning using the TGT model assisted by mission-based snakes and ladders media and learning using the PBL model assisted by learning video media; 3) test the effectiveness of using the TGT model assisted by mission-based snakes and ladders media on learning motivation; 4) test the effectiveness of using the TGT model assisted by mission-based snakes and ladders media on learning outcomes. The method used in this research is quantitative with the type of research Quasi-Experimental Design with Posttest-Only Control Group Design. This research was conducted on third grade students of SDN Sadeng 01 and SDN Sadeng 03. The research sample consisted of 51 students, 29 in the experimental class and 22 in the control class. Data collection used observation, interviews, motivation questionnaires, and tests. Data analysis techniques used independent sample t-test and one sample t-test. The independent sample t-test test data for motivation shows tcount> t table, namely 2.770> 2.010 and learning outcomes show tcount> t table, namely 3.182> 2.010. One sample t-test test data for learning motivation shows tcount> t table, namely 7,166> 2,048 and learning outcomes tcount> t table, namely 8,120> 2,048. Therefore, it can be said that the experimental and control groups averages is different and the teams games tournament model supported by mission-based snakes and ladders media is useful for increasing student motivation and learning outcomes.